Hunting and Fishing in the Neolithic and Eneolithic : Weapons, Techniques and Prey - Selena Vitezovic; Christoforos Arampatzis (Archaeopress Access Archaeology, 2024)
Hunting and fishing in the Neolithic and Eneolithic explores the extent of hunting and fishing activities, their role and importance in subsistence and also their place in social relations. The book contains 13 papers on hunting and fishing techniques, weapons and prey in the area from Anatolia to the Gibraltar region. The range of topics includes technological, typological and functional analyses of weapons used, analyses of hunting and fishing strategies and techniques, and zooarchaeological analyses of the role of hunted fauna in the economy and other aspects of lives of the past communities. Papers include specific case studies as well as syntheses of wider data sets and provide the latest methodological and theoretical perspectives on the role of hunting and fishing in early agricultural societies.